2021
DOI: 10.1155/2021/6686283
|View full text |Cite
|
Sign up to set email alerts
|

Phenetic and Molecular Diversity of Nitrogen Fixating Plant Growth Promoting Azotobacter Isolated from Semiarid Regions of India

Abstract: In the present study, 24 Azotobacter strains were isolated from soils of different areas of southern Rajasthan and characterized at biochemical, functional, and molecular levels. The isolated Azotobacter strains were gram negative and cyst forming when viewed under the microscope. These strains were also screened for their plant growth promoting activities and the ability of these isolates to survive under abiotic stress conditions viz. salt, pH, temperature, and drought stress. All the isolates showed IAA, si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 31 publications
0
15
0
Order By: Relevance
“…Rhizobacteria can act as stimulants and produce hormones such as auxins and gibberellins to help promote plant growth ( Jain et al, 2021 ). Salinity stress can inhibit enzyme activity and cause metabolic changes in plant cells due to the accumulation of too high salts in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Rhizobacteria can act as stimulants and produce hormones such as auxins and gibberellins to help promote plant growth ( Jain et al, 2021 ). Salinity stress can inhibit enzyme activity and cause metabolic changes in plant cells due to the accumulation of too high salts in the cytoplasm.…”
Section: Discussionmentioning
confidence: 99%
“…Different species of Azotobacter fix 20–40 Kg/ha/year of nitrogen and inoculation of selected strains enhanced germination and vigour of young plants along with grain yield in wheat ( Kader et al, 2002 ). Jain et al (2021) found that all the isolated 24 Azotobacter strains showed IAA, siderophore, HCN, and ammonia production, whereas seven Azotobacter strains showed phosphate solubilization. Significant diversity was revealed among all the isolates by Amplified Ribosomal DNA Restriction Analysis (ARDRA) and the dendrogram differentiated twenty-four of the strains into two major clusters at a similarity coefficient of 0.64.…”
Section: Types Of Biofertilizersmentioning
confidence: 95%
“… Types of biofertilizer Bacterial strain used Plant growth promoting activity Effect on plant productivity parameters References Nitrogen- fixing bacteria Azotobacter sp. strain Avi2 (MCC 3432) Nitrogen fixation, production of IAA, siderophore improved vegetative and reproductive growth in rice Banik and Dangar, 2019 Azotobacter chroococcum, A. vinelandii Nitrogen fixation, P solubilization, production of NH 3 , HCN, IAA Increased shoot and root length, leaf and root number, chlorophyll content of maize Jain et al, 2021 Herbaspirillum seropedicae (strain ZAE94) Nitrogen fixation, production of siderophore, IAA Enhanced mineral uptake, increased diameter, weight, length of ear, number of grains/rows, cob weight and grain yield Ávila et al, 2020 Enterobacter cloacae (PGLO9) Nitrogen fixation, phosphorous solubilization, siderophore production, ACC deaminase Enhanced potato growth and yield, significant increase in vegetative growth parameters including root and shoot length, root as well as shoot biomass Verma and Agrawal, 2018 Bradyrhizobium sp. Nitrogen fixation, siderophore and IAA production, P solubilisation Increased vegetative parameters and seed yield in mung bean Alkurtany et al, 2018 Rhizobium meliloti Nitrogen fixation, production of siderophore and chitinase Increased growth and yield, pods quality and better use of nitrogen in peanut Mondal et al, 2020 Phosphate-solubilizing bacteria (PSB) Pseudomonas stutzeri (CSP03), Bacillus subtilis (TTP02), Pseudomonas putida (PHP03) Solubilization of P and zinc, IAA, N 2 fixation, siderophore, NH 3 production Enhanced plant growth in arid soils El-Sayed et al, 2014 Alcaligenes faecalis sub sp.…”
Section: Mechanisms Of Action Of Beneficial Microbesmentioning
confidence: 99%
See 1 more Smart Citation
“…Inoculation of Bradyrhizobium japonicum in soybean plants improved plant biomass, nodulation, and N fixation (Htwe et al, 2019 ). Azotobacter chroococcum improved the plant height and chlorophyll content in maize plants (Jain et al, 2021 ). Bradyrhizobium sp.…”
Section: Types Of Biofertilizers and Their Role In Crop Production An...mentioning
confidence: 99%